The Dynamics of Economic Status Differences in Marriage (A Case Study in Sumbersari, Jember): Dinamika Perbedaan Status Ekonomi dalam Pernikahan (Studi Kasus di Kecamatan Sumbersari Jember) - Kemal Luthfi; Ibnu Zaid Al Atsari; Ardi Arman Syahada; Muhammad Farhan Hadi K. (Al-Zaujiyyah: Jurnal Hukum Keluarga Islam, 2024)
Marriage is a very meaningful moment for every human life in the form of an inner birth relationship between husband and wife. Nikah linguistically is gathering and in terms of sharia is the term of a famous contract consisting of pillars and conditions. In running a marriage, there are many hustles and bustle in it, one of which is the difference in economic status. Differences in economic status are differences in one's position or position in the sector of property income obtained by a person in meeting his living needs. Sumbersari is a sub-district in Jember Regency, East Java Province. The purpose of this study is to determine the phenomenon, the impact of differences in economic status in marriages of the Sumbersari community as well as the opinions of mahzhab and contemporary scholars about the difference in economic status in marriage. This research uses a qualitative approach with case study research types. The results of this study show that: (1) the phenomenon of differences in economic status in marriage is divided into 2 parts; The upper middle class and the lower middle society. (2) Differences in economic status have both positive and negative impacts on marriage. (3) The opinions of madhhab and contemporary scholars are divided into 2 parts; encourage, and allow.